THE EFFECT OF TRAINING PROGRAM IMPLEMENTATION, EMPLOYEE MOTIVATION, AND WORK ENVIRONMENT ON INCREASING EMPLOYEE PRODUCTIVITY AT PT PETROKIMIA GRESIK - Deril Hijriani Auliyah (Adisam Publisher, 2025)
Employee productivity remains a major challenge in human resource management within the industrial sector, including at PT Petrokimia Gresik. Although various training programs have been implemented, their effectiveness in improving productivity has not been systematically measured. This study aims to empirically examine the influence of training, motivation, and work environment on employee productivity. Using a quantitative approach, a survey was conducted with 310 employees who participated in training programs between January and July 2024, selected through simple random sampling. Data were analyzed using multiple linear regression. The results indicate that all three variables—training, work motivation, and work environment—have a positive and significant effect on productivity, both simultaneously and partially. However, employee participation in training remains uneven, indicating an implementation gap. This study highlights the need for a stronger training evaluation system, more adaptive program designs tailored to individual needs, and managerial interventions to foster a more supportive and motivating work environment. The findings reinforce the strategic importance of human resource development in enhancing productivity and provide practical insights for designing more responsive and results-oriented training policies. Further research using a longitudinal approach is recommended to assess the long-term impact of training on employee productivity.